An electrochemical sensor based on TiO2/activated carbon nanocomposite modified screen printed electrode and its performance for phenolic compounds detection in water samples. Issue 3 (19th February 2016) - Hayat, Akhtar; Rhouati, Amina; Mishra, Rupesh K.; Alonso, Gustavo A.; Nasir, Muhammad; Istamboulie, Georges; Marty, Jean Louis
ABSTRACT: Herein, we reported a titanium oxide (TiO2 ) modified activated carbon nanocomposite that showed advantageous characteristics in terms of electro-conductivity, catalytic activity and surface area. The designed nanocomposite was employed to modify the screen printed carbon electrode transducer surface in the construction of an electrochemical sensor. The electrode surface modification was characterised by cyclic voltammetry and impedimetric studies. The modified transducer surface was subsequently used for the detection of four phenolic endocrine disruptors, p -nitrophenol, hydroquinone, catechol and 1-naphtol. Under optimal conditions, TiO2 modified activated carbon sensor was evaluated by differential pulse voltammetry showing a good linearity with correlation coefficients higher than 0.99. It showed, in parallel, a high sensitivity where the detection limits were 348 ng/L, 110.1 ng/L, 3.3 ng/L and 7.2 µg/L for the respective studied compounds (S/N = 3). Finally, we validated the method with river water samples, and good recovery values were obtained showing the potential application of the reported biosensor.